A Comperative Adaptation of the Crick Learning for Resilient Agency (CLARA) with Classical Test Theory and Item Response Theory - Ruth Crıck; Shaofu Huang; Ömer Kutlu; Hasan Fehmi Özdemir (International Journal of Assessment Tools in Education, 2022)
The aim of this study is to adapt the Crick Learning for Resilient Agency (CLARA) to Turkish culture, and to examine the psychometric features of the Inventory according to both Classical Test Theory (CTT) and Item Response Theory (IRT). In this respect, it is a descriptive level survey design research. Two different study groups were formed in accordance with the purpose of the study. Lingual equivalence applications were performed on two separate groups, one of which consisted of English Language and Literature Department students and the other consisted of English Language instructors. 1054 students participated in the validity and reliability studies from 101 different undergraduate programs at Ankara University. Before testing the research questions, it was examined whether the assumptions of CTT and IRT were met. With the application data; the predicted item discrimination indices, ability levels, students’ scores forming their learning power profiles, and reliability coefficient values were found to be similar in both theories. It can be said that with CLARA-Tr, obtained by adapting CLARA, a valid and reliable tool has been provided to the Turkish literature to be used in future studies.